PENGARUH PENGGUNAAN INTERNET,KONSUMSI LISTRIK DAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DI JAWA DAN BALI - Muhammad Ikhsan; Dewi Zaini Putri (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to determine whether there is an influence between the use of the Internet, electricity and labor on economic growth in Java and Bali. The data used are secondary data in the form of panels with a period of time from 2015 to 2017, with the technique of collecting documentation data and literature studies obtained from relevant institutions and agencies. The variables used are Economic Growth, Internet Usage, Electricity Consumption and Labor. The research method used is the Panel Regression Model. The results showed that: (1) there was a positive and significant relationship between Internet Usage on Economic Growth (2) Ithere was a negative and significant relationship between Electricity Consumption and Economic Growth (3) there was a positive and insignificant relationship between Labor andIEconomic Growth.